Analgesic, anti-inflammatory and anti-hyperlipidemic activities of Commiphora molmol extract (Myrrh) - Shalaby, Mostafa Abbas (J Intercult Ethnopharmacol, 2014)
AIM: The aim was to evaluate the analgesic, anti-inflammatory, and anti-hyperlipidemic activities of Commiphora molmol extract (CME) and its effects on body weight and blood lipids. MATERIALS AND METHODS: The analgesic effect was assessed using thermal (hot plate test) and chemical (writhing test) stimuli to induce central and peripheral pain in mice. The anti-inflammatory activity was determined using formalin-induced paw edema in rats. For anti-hyperlipidemic effect, 25 rats were randomly divided into five groups (n = 5). Group 1 was fed on basal diet (normal control), while the other four groups were fed on high-fat diet for 6 weeks to induce obesity and hyperlipidemia. Thereafter, Group 2 was kept obese hyperlipidemic, and Groups 3, 4 and 5 were orally given CME in doses of 125, 250, and 500 mg/kg for 6 weeks, respectively. Body weight gains of rats were calculated, and blood samples were collected for analysis of blood lipids. RESULTS: CME produced a dose-dependent analgesic effect using both hot plate and writhing tests in mice. The hot plate method appeared to be more sensitive than writhing test. CME exhibited an anti-inflammatory activity as it decreased volume of paw edema induced by formalin in rats. The extract decreased body weight gain; normalized the high levels of blood lipids and decreased atherogenic index low-density lipoprotein/ high-density lipoprotein in obese hyperlipidemic rats. CONCLUSION: The results denote that C. molmol extract (myrrh) has significant analgesic, anti-inflammatory and anti-hyperlipidemic effects and reduces body weight gain and improves blood lipids profile. These results affirm the traditional use of C. molmol for the treatment of pain, inflammations, and hyperlipidemia.